Comparing physical quality of eggs between different chicken types - Bódi, László; Thieu Ngoc, Lan Phuong; Kovácsné Gaál, Katalin; Konrád, Szilárd; Barta, Ildikó; Kisné Do thi, Dong Xuan; Szentes, Katalin Ágnes; Szalay, István; Lencsés, György (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
4 chicken genotypes (2 stocks of indigenous Yellow Hungarian chicken breed, Mosonmagyaróvár and Gödöllő (SMO and SMG), 2 dual purpose breeds (New Hampshire – NHS and White Plymouth – WPM) and Hy-Line brown layer hybrid (HYL)) were used to study physical quality of eggs of different types of chicken. Egg weight, egg height, egg width, egg shape index, egg white-, egg yolk-, eggshell weight, strength and thickness, as well as correlation of these traits were examined. Statistical analyses showed significant effect of genotype on most of egg quality traits. Yellow Hungarian layers produced longer eggs with higher egg yolk % than NHS, WPM and HYL. SMG eggs were markedly lighter than NHS, WPM and HYL eggs. However, SMG eggshell was significantly stronger than SMO and HYL. Significant positive correlations between egg weight-egg height; egg weight-egg width and negative ones between egg white weight-egg yolk weight were found in all groups. Additionally, there were significant negative correlations between egg weight, eggshell weight and eggshell thickness of NHS and WPM eggs. Results of this study suggest that all physical traits except egg weight are the same or seem better in the eggs of the unselected local breed (Yellow Hungarian) than of selected breeds or the layer hybrid. Among the superior traits of local breed, egg yolk ratio, eggshell strength or the correlation between egg weight and egg yolk weight should be stressed.